Discovery of Unforeseen Energy-Transfer-Based Transformations Using a Combined Screening Approach - Strieth-Kalthoff, Felix; Henkel, Christian; Teders, Michael; Kahnt, Axel; Knolle, Wolfgang; Gomez-Suarez, Adrian; Dirian, Konstantin; Alex, Wiebke; Bergander, Klaus; Daniliuc, Constantin G.; Abel, Bernd; Guldi, Dirk Michael; et al. (Chem, 2019)
The discovery of novel (catalytic) transformations and mechanisms is commonly based on rational design. However, many discoveries have resulted directly from experimental serendipity. Building on this, we report a two-dimensional screening protocol, combining "mechanism-based" and "reaction-based" screening and its application to the field of visible light photocatalysis. To this end, two energy-transfer-based cycloaddition reactions could be realized: a notably endergonic energy transfer process allows for the dearomative cycloaddition of benzothiophenes and related heterocycles. Moreover, by sensitization of enone moieties, a [2+2]-cycloaddition to alkynes and an unexpected cycloaddition-rearrangement cascade were discovered. Advanced spectro-scopic techniques (in particular transient absorption spectroscopy and pulse radiolysis) were utilized to investigate the underlying photophysical processes and gain insight into reaction kinetics. Combining these results with further mechanistic analysis can eventually turn out to be helpful upon knowledge-driven development of improved systems. Such screening approaches can thus provide complementary access toward novel and more efficient catalytic protocols.
CRIS-Team WoS Importer:2019-08-27